2008
DOI: 10.1002/pon.1279
|View full text |Cite
|
Sign up to set email alerts
|

Support needs and acceptability of psychological and peer consultation: attitudes of 108 women who had undergone or were considering prophylactic mastectomy

Abstract: Summary Prophylactic mastectomy (PM) offers 90% or greater reduction in risk of breast cancer to women at increased hereditary risk. Nonetheless, acceptance in North America has been low (0–36%). Most women report reduced cancer worry post-operatively, but up to 25–50% of women electing surgery also report psychological distress and/or difficulty adapting following PM. Psychological consultation to aid decision-making and improve post-surgical coping isn’t routinely offered. This retrospective, cross-sectional… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

6
38
0
4

Year Published

2008
2008
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 32 publications
6
38
0
4
Order By: Relevance
“…stanford.edu; accessed March 11, 2014) demonstrated that both BRCA1/BRCA2 mutation carriers and local clinicians noted that the tool was easy to use, clinically relevant, and they believed it could improve patientphysician encounters (mean scores, 4.50 and 4.69, respectively, on a 1-5 scale). 133 Research also supports the use of psychological consultation for women who are considering prophylactic mastectomy 134 as well as prophylactic bilateral salpingo-oophorectomy. 135 Both presurgical counseling and postsurgical psychosexual follow-up can aid in adjusting, even up to 3 years postsurgery.…”
Section: Discussionmentioning
confidence: 97%
“…stanford.edu; accessed March 11, 2014) demonstrated that both BRCA1/BRCA2 mutation carriers and local clinicians noted that the tool was easy to use, clinically relevant, and they believed it could improve patientphysician encounters (mean scores, 4.50 and 4.69, respectively, on a 1-5 scale). 133 Research also supports the use of psychological consultation for women who are considering prophylactic mastectomy 134 as well as prophylactic bilateral salpingo-oophorectomy. 135 Both presurgical counseling and postsurgical psychosexual follow-up can aid in adjusting, even up to 3 years postsurgery.…”
Section: Discussionmentioning
confidence: 97%
“…Com o intuito de reduzir os níveis de ansiedade, melhorar o bem-estar do paciente, aumentar a adesão ao tratamento, torná-lo mais apto para enfrentar com maior eficiência o procedimento cirúrgico, proporcionar um processo de recuperação pós-operatória mais rápido e humanizar os cuidados cirúrgicos dispensados aos pacientes, alguns estudos apontam a efetividade de diversas intervenções preparatórias, vinculadas ao perfil comportamental e cognitivo dos pacientes, tais como: a) disponibilizar adequado nível de informação às necessidades do paciente, que devem ser identificadas previamente pelos profissionais de saúde (Bellani, 2008;Gilmartin & Wright, 2007;Juan, 2005; Rankinen et at., 2007;Shelley & Pakenham, 2007); b) promover modificações na estrutura física dos ambientes pré e pós--operatório, tornando-os espaços acolhedores, privativos, calmos e relaxantes (Gilmartin & Wright, 2007); c) utilizar técnicas de relaxamento muscular progressivo ou relaxamento induzido, por meio de visualização ativa no pré e pós-operatório (Ribeiro et al, 2002;Rosendahl et al, 2009); e d) disponibilizar suporte espiritual e atender às necessidades psicossociais dos pacientes, viabilizando estratégias de enfrentamento cognitivo, baseadas no problema a ser enfrentado (Patenaude et al, 2009;Rosendahl et al, 2009). …”
Section: This Paper Aims To Identify Information On the Main Types Anunclassified
“…A transmissão de informações tinha o objetivo de qualificar o paciente com dados técnicos e reduzir a probabilidade de sintomas de ansiedade, que ocorrem mais frequentemente quando o indivíduo é exposto a situações desconhecidas e classificadas como potencialmente aversivas (Bellani, 2008;Collazo-Clavell, Clark, McAlpine & Jensen, 2006;Gilmartin & Wright, 2007; Rankinen et al, 2007;Shelley & Pakenham, 2007) (Gilmartin & Wright, 2007) e o desenvolvimento de atividades por equipes multidisciplinares, embora sejam procedimentos menos referidos, foram apontados como complementares à redução da ansiedade do paciente em condição pré-cirúrgica e potencialmente benéficos a seu bem-estar (Gilmartin, 2004). Rankinen et al (2007) apontaram seis dimensões que devem compor as informações disponibilizadas aos pacientes que são submetidos à cirurgia: a) biofisiológico (doença, sintomas, formas de tratamento e possíveis complicações); b) funcionais (necessidades individuais, mobilidade, descanso, nutrição e higiene corporal); c) empírico (vivência de emoções e experiências no hospital); d) éticas (direitos, deveres, participação na tomada de decisão, privacidade e confidencialidade); e) social (papel da família, relação com outros pacientes e grupos de apoio); e f ) financeiro (custos monetários e benefícios).Marchand et al (2007) destacam que as informações a serem transmitidas dependem do tipo de cirurgia que será realizada, do grau de conhecimento e de organização de que o paciente já dispõe, bem como de sua condição em termos de bem-estar psicológico e de sua desejabilidade em termos de informações.Alguns estudos ainda destacam a necessidade de se analisar o impacto provocado por estas informações, planejando-se antecipadamente o conteúdo a ser disponibilizado, o momento mais adequado para apresentá-lo e os efeitos psicossociais da transmissão, considerando-se ainda as diferenças culturais entre os pacientes (Bellani, 2008;Henderson & Chien, 2004; Krone & Slangen, 2005;Marchand et al, 2007;Patenaude et al, 2009). …”
unclassified
“…This is likely influenced by factors such as cultural variations [29][30][31] , incidence and mortality patterns in relatives [24,31,32] , marital status and earlier pregnancy [24] , having young children, and the doctors' approach in giving information about other preventive strategies [28,31,33] .…”
Section: Psychological Effects Following Mastectomymentioning
confidence: 99%